Neglected cause of retinal detachment: a hospital-based case-control study on occupational heavy lifting as a risk factor - Nayera S. Mostafa; Radwa Nabil El Shereif; Ayat F. Manzour (SpringerOpen, 2021)
Abstract Background Heavy lifting may lead to sudden increase in venous, intra-abdominal, and intraocular pressure which in turn may cause retinal detachment (RD). The epidemiological evidence for this association is still inconclusive. This study was carried out to investigate the relationship between occupational heavy lifting and RD. Methods A case-control study was carried out on 151 RD cases and 113 controls free of RD attending the ophthalmology outpatient clinic at Ain Shams University. Personal, medical, and occupational data were collected using interview questionnaires in addition to conducting full ophthalmologic examination. Results The mean age of study participants was 45.8 ± 9.1 years (46.8 ± 8.9, 44.4 ± 9.2 for RD cases and controls respectively). Statistically significant differences were found between cases and controls regarding years of working, occupational categories, frequency of occupational heavy lifting, non-work heavy lifting, history of head trauma, history of eye surgeries, and family history of RD. Multivariate logistic regression analysis showed that lifting (Odds ratio (OR) = 4.8, p < 0.0001), history of head trauma (OR = 3.3, p = 0.013), diabetes mellitus (DM) (OR = 4.96, p < 0.0001), and previous eye surgeries (OR = 3.5, p = 0.003) increased the risk of RD. Conclusion Occupational heavy lifting is associated with RD. Occupational categories, duration of lifting heavy objects during work and family history of RD had a significant effect on RD. An ergonomic approach should be adopted and practiced as it has a significant impact on reducing the risks of lifting and carrying heavy objects. The workplace's design (including having appropriate mechanical aids available) is also of significant importance to reducing the risks. During the patient's visit, ophthalmologists should consider and look for the occupational heavy lifting history as a potential risk factor of the patient's symptoms.